2008
DOI: 10.1016/j.optcom.2008.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Collision in double random phase encoding

Abstract: a b s t r a c tCollision is a situation that occurs when two or more distinct inputs into a security system produce identical outputs, which is undesirable in some security applications. This is especially true of the applications of watermarking and authentication. In this manuscript we present a study of the collision property of double random phase encoding. We show that one can produce meaningful collisions from the cyphertext of a watermark embedded in a host image by use of phase retrieval techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…However, care would have to be taken when specifying a very efficient optical implementation for the irreversible function f 1 in CFB and OFB. The most efficient nonlinear operation in analog optics (square law detection) could be susceptible to phaseretrieval techniques and, as has been mentioned, DRPE itself cannot be used as a cryptographic hash function [45]. In particular, the perfect calculation of f 1 in the OFB mode is required in order to avoid the propagation of errors, and so it would be recommended that this step be carried out with digital optics or digital electronics.…”
Section: Discussion On Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, care would have to be taken when specifying a very efficient optical implementation for the irreversible function f 1 in CFB and OFB. The most efficient nonlinear operation in analog optics (square law detection) could be susceptible to phaseretrieval techniques and, as has been mentioned, DRPE itself cannot be used as a cryptographic hash function [45]. In particular, the perfect calculation of f 1 in the OFB mode is required in order to avoid the propagation of errors, and so it would be recommended that this step be carried out with digital optics or digital electronics.…”
Section: Discussion On Implementationmentioning
confidence: 99%
“…The irreversible f 1 operation can be implemented elsewhere (in optics or electronics). It has been shown [45] that DRPE itself should not be used for the irreversible f 1 . In such a scenario, DRPE encryption is defined as…”
Section: E Cipher Feedback Modementioning
confidence: 99%
“…There has been significant interest in encryption schemes which can be implemented optically [18][19][20][21][22][23]. Practical optical implementation of such systems is difficult [19,22] and the security and robustness of these systems is still a matter of study and analysis [18,[20][21][22][23].…”
Section: Optical Encryptionmentioning
confidence: 99%
“…Practical optical implementation of such systems is difficult [19,22] and the security and robustness of these systems is still a matter of study and analysis [18,[20][21][22][23]. However not only do such systems pose a very interesting problem for the fast algorithms described above in Section 3, it has been shown that the problems of encryption and multiplexing can be discussed fruitfully using PSO [24].…”
Section: Optical Encryptionmentioning
confidence: 99%
“…Importantly the resulting framework has also supplied a set of mathematical modelling tools, which have provided some insights into the operation of such systems. Some of the applications examined by my group include metrology systems [2][3][4][5][6]25], and optical encryption [18][19][20][21][22][23][24]31]. The work has included significant experimental work with speckle based and holographic systems [4][5][6][7][8][9][10][11]32].…”
Section: Introductionmentioning
confidence: 99%